A Successful Pharmacist-Based Quality Initiative to Reduce Inappropriate Stress Ulcer Prophylaxis Use in an Academic Medical Intensive Care Unit - Umair Masood MD; Anuj Sharma MD; Zabeer Bhatti MD; Jessica Carroll BSc; Amit Bhardwaj MD; Devamohan Sivalingam MD; Amit S. Dhamoon MD, PhD (SAGE Publishing, 2018)
Stress ulcer prophylaxis (SUP) is often inappropriately utilized, particularly in critically ill patients. The objective of this study is to find an effective way of reducing inappropriate SUP use in an academic medical intensive care unit (ICU). Medical ICU patients receiving SUP were identified over a 1-month period, and their charts were reviewed to determine whether American Society of Health-System Pharmacists guidelines were followed. Inappropriate usage was calculated as inappropriate patient-days and converted to incidence per 100 patient-days. Two interventions were implemented: (1) Pharmacists reviewed indications for SUP on each patient during daily team rounds and daily medication reconciliation and (2) residents rotating on ICU services were educated on a bimonthly basis. Postintervention data were obtained in a similar fashion. Prior to intervention, the incidence of inappropriate SUP usage was calculated to be 26.75 per 100 patient-days (n = 1099 total patient-days). Total cost attributable to the inappropriate use was $2433. Post intervention, we were able to decrease the inappropriate incidence of SUP usage to 7.14 per 100 patient-days (n = 1149 total patient-days). In addition, total cost of inappropriate use was reduced to $239.80. Our study highlights an effective multidisciplinary approach to reduce the inappropriate use of SUP in an academic medical ICU. We were able to reduce the incidence of inappropriate use of SUP by 73.31% ( P < .001). Furthermore, we were able to decrease the costs by approximately $2200/month.